2013
DOI: 10.12816/0003648
|View full text |Cite
|
Sign up to set email alerts
|

Micro Financing and Entrepreneurial Development In Nigeria ; the Mediating Role of Marketing

Abstract: Micro finance bank that is popularly known as bank for the poor is basically established to alleviate poverty and also to serve as a platform for promoting entrepreneurial development. The question is; to what extent has it been able to fulfil its basic functions in Nigeria? The primary objective of this study is to ascertain the extent to which micro financing has contributed to entrepreneurial development and also to find out the extent to which marketing techniques have be employed for effective and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The entrepreneurial growth could be significant with MFBs if it works for the development of the production sector if the MFBs were managed and operated properly to achieve the basic goal of their foundation. It was recommended by the researcher to provide MF to the poor to encourage them and to avoid default risk, encourage group borrowing, Government policies adopted to provide knowledge to borrowers, give awareness to borrowers, make policies for loan repayment issues, and need to introduce more factors that affect entrepreneurial growth (Unam & Unam, 2013;Akinbola et al 2013). Salum (2014) concluded that Microfinance institutions were playing a very important role in boosting up entrepreneurial development at the micro-level and also identifying the different types of hindrances in business progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The entrepreneurial growth could be significant with MFBs if it works for the development of the production sector if the MFBs were managed and operated properly to achieve the basic goal of their foundation. It was recommended by the researcher to provide MF to the poor to encourage them and to avoid default risk, encourage group borrowing, Government policies adopted to provide knowledge to borrowers, give awareness to borrowers, make policies for loan repayment issues, and need to introduce more factors that affect entrepreneurial growth (Unam & Unam, 2013;Akinbola et al 2013). Salum (2014) concluded that Microfinance institutions were playing a very important role in boosting up entrepreneurial development at the micro-level and also identifying the different types of hindrances in business progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although social business fund is not similar with microcredit, the impact on growth on microenterprises could be similar or more robust than the microcredit because social business fund has overcome the problems of mandatory weekly or monthly repayment system of microcredit. Most of the previous literature has found relationship between access to finance and enterprise growth as a proxy of entrepreneurship development [3][4][5][6][7]. The Grameen Companies providing fund for the Nobin Udyokta Program are playing the role like venture capitalist firm.…”
Section: Access To Finance and Entrepreneurship Developmentmentioning
confidence: 99%